Simulasi Manajemen Komunikasi Tambang Pasir Galian C Antara Perusahaan dan Pemerintah Daerah - Basuki Rahmat Hakim (Jurnal Jaringan Telekomunikasi, 2017)
The purpose of making this system is to monitor the purchase of excavated sand C to reduce fraudulent payment of levies by mine owners and make it easier for DISPENDA to control mining vehicles. This system uses 2 pieces of RFID which are used to identify vehicle numbers that leave and enter the mine. At the entrance and exit of the mine there is a load cell that is used forweighing the weight of sand which is used as the basis for the levy value and the price of sand. From the results of the load cell test, it shows that the calibration results were carried out well. This is proven by the measurement accuracy of the load cell. Based on data from test resultsQOS where the average value of transmission delay is 113.5 ms, throughput is at 0.077 mbit / sec - 0.138 mbit / sec and packet loss is 0.0%. In accordance with the TIPHON standard, this situation belongs to a very good range.